2016
DOI: 10.17795/zjrms-6250
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Rate of Vulvovaginal Candidiasis and Identification of Candida Species in Women in Referred to Hamedan Hospitals 2013 - 2014, West of Iran

Abstract: Background: Vulvovaginal candidiasis is a common gynecological finding among the women worldwide. Objectives: In this study determine of prevalence rate of vulvovaginal candidiasis and identification of Candida species was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In the present study, a different frequency of VVC (39.76%) was reported when compared to our previous studies in Ahvaz in 2016 (28.3%) and 2010 (49%) (15,21). The frequency of VVC in other cities in Iran was reported as 62.1%, 43.3%, 40%, 26%, and 4.8% from Ilam, Babol, Arak, Hamadan, and Zanjan, respectively (12,13,16,31,32).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, a different frequency of VVC (39.76%) was reported when compared to our previous studies in Ahvaz in 2016 (28.3%) and 2010 (49%) (15,21). The frequency of VVC in other cities in Iran was reported as 62.1%, 43.3%, 40%, 26%, and 4.8% from Ilam, Babol, Arak, Hamadan, and Zanjan, respectively (12,13,16,31,32).…”
Section: Discussionmentioning
confidence: 98%
“…Researchers believe that 5 -8% of adult women have RVVC (5,6,11). Several studies have shown that the frequency of VVC varies in different provinces of Iran, from 4.8 to 73% (12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Vulvovaginal candidiasis is one of the most common fungal infections among middle-aged Iranian women (Mahmoudabadi et al, 2010; Rad et al, 2011; Mohammadi-Ghalehbin et al, 2016; Rezaei-Matehkolaei et al, 2016). Several frequencies of the disease have been reported from different provinces in Iran including 62.1, 43.3, 40, 26, and 4.8% from Ilam, Babol, Arak, Hamadan, and Zanjan, respectively (Jamilian et al, 2007; Bahram et al, 2009; Esmaeilzadeh et al, 2009; Mohamadi et al, 2015; Habibipour, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to Habibipour R, [17]C. albicans (81.3%) predominantly and then C. glabrata (11%), C. tropicalis (4.4%) and C. kuresi (2.2%) were isolated from VVC.…”
Section: Discussionmentioning
confidence: 99%